Making Space for Social and Emotional Learning in Science Education - Ingram, Erin; Reddick, Kristie; Honaker, Jessica M.; Pearson, Gwen A. (Frontiers in Education, 2021)
Social-emotional learning (SEL) is known to improve student outcomes but is rarely combined with STEM. In this paper we present an action research study to examine the impact of a STEM + SEL curriculum intervention to address a real-world school conflict. One hundred 6th - 8th graders and 4 teachers participated in an in-person facilitation of a SEL Arthropod curriculum, DIFFERENT. After the intervention, students completed open-ended couplet statements about arthropod behavior, tarantulas, and humans designed to measure sentiment change. Answers were manually coded using inductive coding on a scale of negative (1) to positive (5). Statement sentiments significantly shifted from negative to neutral and negative to positive for all 3 questions. Neutral to positive shifts were only significant for the couplet statements about arthropod behavior. This study reports the first confirmed instance of successful use of arthropods for SEL within a curriculum that integrates students’ social-emotional skills within a science classroom.